The impact of the labour inspection and enforcement strategy on occupational health and safety : the case of Tzaneen Labour Centre Limpopo Province - Malope, Prudence Nomthandazo (My University, 2021)
The study explored the impact of Labour inspection and enforcement strategy on Occupational Health and Safety with specific reference to Tzaneen Labour Centre in the Limpopo Province. The international Labour Organisation (ILO) 2017 world statistics indicate that 2.3 million women and men around the world succumb to work-related accidents or diseases every year and this corresponds to over 6 000 deaths every single day. The Department of Labour (DOL) Annual Reports (2007) indicates that in the Province of Limpopo, 1 717 workplaces were inspected to determine compliance with Occupational Health and Safety and only 825 were found to be compliant. Literature indicate that most accidents and fatalities at the workplace are primarily due to reluctance by employers to provide safety clothing and equipment, lack of proper training on OHS, lack of safety policy and enforcement procedures, poor safety consciousness among workers and lack of strict operational procedures amongst others. A qualitative approach was used to conduct this study and a case study was selected as the most direct method to conduct the study and obtain insight. Interviews were conducted with DOL managers, OHS inspectors and farm employers. Questionnaires were administered to farmworkers. The study revealed that there are few OHS inspectors at the Tzaneen Labour centre hence inspections are very minimal at the farms, this can assist in increasing number of places to be inspected and enforcing compliance. Findings also indicate that most farm employees are not cognisant with the OHS policies enacted to protect them and OHS records non-existent on many farms. The study recommends further rigorous training of the OHS inspectors, beefing up their numbers and equipping them with safety clothing and detection gadgets
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Labour inspection; Occupational Health and Safety; Tzaneen Labour Centre; Indusrial hygiene; Industrial safety